A low‐power and area‐efficient ultrasound receiver using beamforming successive approximation register analog‐to‐digital converter with capacitive digital‐to‐analog converter combined delay cell structure for 3‐D imaging systems. Issue 22 (19th September 2022) - Lee, Seungah; Yun, Soohyun; Bae, Joonsung
Abstract: The authors present a low‐power area‐efficient subarray beamforming receiver (RX) structure for a miniaturized 3‐D ultrasound imaging system. Given that the delay‐and‐sum (DAS) and digitization functions consume most of the area and power in the receiver, the beamforming successive approximation register (SAR) analog‐to‐digital converter (ADC) shares its capacitive digital‐to‐analog converter (CDAC) with the delay cells. As a result, the delay cells implemented with capacitors are embedded in the CDAC with significant area reduction, further eliminating the need for power‐hungry ADC buffers. Furthermore, the dual reference 10‐bit SAR ADC reduces the area of CDAC by 32 times, achieving a switching energy reduction of 98.3%, compared to the conventional SAR ADC. As a result, the proposed beamforming SAR ADC, simulated using a 0.18 μm CMOS process, consumes 230 μW per channel, significantly reducing the per channel capacitance.